Timor Zone: Slave Trading Network from the Traditional Era to the Late Nineteenth-Century Dutch Colonial State - Fanada Sholihah; Yety Rochwulaningsih; Singgih Tri Sulistiyono (Jurnal Sejarah Citra Lekha, 2023)
This article examines the continuity and changes of the Timorese slave trade network from the traditional era to the late nineteenth-century Dutch colonial state. Archival records, newspapers, and other literature were used extensively to reconstruct the map of the Timorese slave trading. Grasping the dynamics of change and trade networks of Timor, there were two proposed research questions:  First, how did the Timorese slave trading network experience continuity and change from the traditional period until the late nineteenth-century Dutch colonial state? Second, to what extent does the need for labour in the global and Southeast Asian context play in shaping and catalyzing the expansion of the Timorese slave network? Timor and its surroundings were deemed slave enclaves (peripheries) with several trading centres. Traditionally, slave trade routes formed from Timor to Java and Malacca. In addition, it was intended for Dili and Macau during the Portuguese era. During the VOC era, Batavia and Banda were the busiest routes of the Timorese slave trade. Networking was increasingly across-the-board, along with the need for labour to meet the demands of the global market. Henceforward, during the Dutch East Indies, the slave trading network continued expanding to Maurits, Réunion, Macau, Mozambique, and Mombasa and several years after the post-prohibition of slavery, leaving Ende Bay as the only centre of the slavery trade.